Study of the Inclusion Complexation of Sodium Diclofenac-3-amino-β-cyclodextrin and Determination of the Stability Constant by UV-Vis Spectroscopy - GHARIB NASERI, NAHID; ASHNAGAR, ALAMDAR; SHALGAHIAN, ZAL (Asian Journal of Chemistry, 2010)
Because of its therapeutical importance, sodium diclofenac has a widespread use. In this work, the complexation between sodium diclofenac and 3-amino-β-cyclodextrin was studied. The stability constant (K) of the complex was determined.